Incidence of Scaphoid Fractures and Associated Injuries at US Trauma Centers - Wells, Matthew E.; Nicholson, Tyler C.; Macias, Reuben A.; Nesti, Leon J.; Dunn, John C. (Journal of Wrist Surgery, 2020)
Backgound The scaphoid is the most commonly fractured carpal bone and often presents as a diagnostic challenge. Fractures can often go unnoticed on initial radiographic evaluation and clinical presentation can vary significantly among patients. Awareness of high-risk cohorts assists practitioners in making the appropriate clinical diagnosis of acute scaphoid fracture.Materials and Methods The National Trauma Data Bank is the world's largest trauma data repository. Utilizing the 2016 public use file, we isolated scaphoid fractures by anatomic fracture location by utilizing International Classification of Diseases, 10th revision coding. Reported cases of distal pole (S62.01), waist (S62.02), and proximal pole (S62.03) were included. This data was then queried to determine trends in mechanism of injury, demographic information, and associated injuries.Results There were a total of 968,665 patients with 2,769 cases of reported scaphoid fractures resulting in 286 scaphoid fractures per 100,000 person-years. Males were more likely to sustain a scaphoid fracture than females. The most commonly encountered associated injuries were distal radius fractures, distal ulnar fractures, and nonscaphoid carpal bone fractures, respectively.Conclusions Scaphoid fractures presenting to trauma centers are more commonly reported among males and those involved in motor vehicle accidents or falls. Appropriate scaphoid-specific radiographic imaging should be obtained as well as wrist and elbow images to evaluate for concomitant injuries, especially distal radius fractures.
Keywords: scaphoid fracture; National Trauma Data Bank; trauma; fall; proximal pole; waist; distal pole; incidence